Makna Simbolik Tari Ngadu Tanduk pada Masyarakat Desa Siulak Panjang Kabupaten Kerinci Provinsi Jambi - Saura Arfina Novenda; Anak Agung Istri Agung Citrawati; Ninon Syofia; Wahida Wahyuni (INDO PUBLISHING, 2026)
This study aims to analyze the symbolic meaning contained in the Ngadu Tanduk dance in Siulak Panjang Village, Kerinci Regency, Jambi Province. The Ngadu Tanduk dance is a traditional dance inspired by the buffalo fighting game that once developed in the agrarian community of Siulak Panjang Village. Initially, this dance was performed as community entertainment after the rice harvest, then developed into a cultural performance that was displayed in traditional events and festivals. This study uses a descriptive analysis method. Data collection techniques were carried out through observation, interviews, and documentation by involving dancers, musicians, community leaders, and cultural observers as research informants. Data were analyzed through stages of denotative and connotative meaning based on Roland Barthes' semiotic approach. The results of the study show that the movements in the Ngadu Tanduk dance imitate the behavior of buffaloes before and during the fight in the dance. Connotatively, these movements symbolize respect, readiness, alertness, courage, strength, and fighting spirit. The replica buffalo horn props also symbolize the community's relationship with agrarian life. Overall, this dance reflects the cultural values, identity, and social life of the Siulak Panjang Village community.